Analgesic Effects of Duloxetine on Formalin-Induced Hyperalgesia and Its Underlying Mechanisms in the CeA - Zhang, Lie; Yin, Jun-Bin; Hu, Wei; Zhao, Wen-Jun; Fan, Qing-Rong; Qiu, Zhi-Chun; He, Ming-Jie; Ding, Tan; Sun, Yan; Kaye, Alan D.; Wang, En-Ren (Frontiers in Pharmacology, 2018)
In rodents, the amygdala has been proposed to serve as a key center for the nociceptive perception. Previous studies have shown that extracellular signal-regulated kinase (ERK) signaling cascade in the central nucleus of amygdala (CeA) played a functional role in inflammation-induced peripheral hypersensitivity. Duloxetine (DUL), a serotonin and noradrenaline reuptake inhibitor, produced analgesia on formalin-induced spontaneous pain behaviors. However, it is still unclear whether single DUL pretreatment influences formalin-induced hypersensitivity and what is the underlying mechanism. In the current study, we revealed that systemic pretreatment with DUL not only dose-dependently suppressed the spontaneous pain behaviors, but also relieved mechanical and thermal hypersensitivity induced by formalin hindpaw injection. Consistent with the analgesic effects of DUL on the pain behaviors, the expressions of Fos and pERK that were used to check the neuronal activities in the spinal cord and CeA were also dose-dependently reduced following DUL pretreatment. Meanwhile, no emotional aversive behaviors were observed at 24 hours after formalin injection. The concentration of 5-HT in the CeA was correlated with the dose of DUL in a positive manner at 24 hours after formalin injection. Direct injecting 5-HT into the CeA suppressed both the spontaneous pain behaviors and hyperalgesia induced by formalin injection. However, DUL did not have protective effects on the formalin-induced edema of hindpaw. In sum, the activation of CeA neurons may account for the transition from acute pain to long-term hyperalgesia after formalin injection. DUL may produce potent analgesic effects on the hyperalgesia and decrease the expressions of p-ERK through increasing the concentration of serotonin in the CeA.